PREVALENSI PASIEN GLAUKOMA DENGAN DIABETES MELLITUS TIPE 2 DI RUMAH SAKIT UMUM DAERAH dr. ZAINOEL ABIDIN BANDA ACEH - Eva Mardalena; Feriyani Feriyani (Jurnal Sains Riset, 2021)
Glaucoma is a group of diseases characterized by distinctive optic neuropathy, associated with loss of sight-seeing field with very high intraocular pressure is one of the primary risk factors. Glaucoma itself becomes a disease that the incidence of good world, Indonesia and even Aceh have increased and can cause blindness. The purpose of this study was to determine the demographic data of cataract patients with comorbid conditions in the form of diabetes in RSUDZA. This research is a type of observational descriptive research with cross sectional design, by approach, observation or data collection at one time. The result of the research shows that the respondent's sex is the most common are 39 respondents (59.1%), while the female sex is 32 respondents (45.1%). Meanwhile, in terms of age 41 responden its (57.8%) who were patients with age group 46 to 65 years continued to follow 27 respondents age group 65 years (38%). In the age group 26 to 45 years Jound 2 respondents (2.8%) and the age group 12 to 25 years obtained I respondent (1.4%). The conclusion of this study is that more male sex suffering from glaucoma with type 2 diabetes mellitus and age became one of the major risk factors coupled with comorbid namely diabetes mellitus which became an enhancer factor for the emergence of glaucoma with diabetes mellitus.Keywords: Glaucoma, diabetes, gender, age